A Neighbor Discovery Algorithm in Network of Radar and Communication Integrated System - Jinming Li; Laixian Peng; Yilei Ye; Renhui Xu; Wendong Zhao; Chang Tian (2014 IEEE 17th International Conference on Computational Science and Engineering, 2014)
Networking Radar-Communication Integrated System (RCIS) promises an improved performance of radar and communication system platform by expanding scanning range and sharing information with each other. But equipping RCIS with directional antennas, in return, will worsen network's connectivity. In this paper, we aim to address the problem of neighbor discovery stage in networking process. Then, we are to present a directional neighbor discovery algorithm called scan based networking radar algorithm, or, SBA-RA. The difference between SBA-RA and previous researches which assume no prior knowledge of neighbors, is that SBA-RA makes full use of the approximate location information of neighbors obtained from RCIS platform to accelerate neighbor discovery. What is more, the performance of SBA-RA in RCIS is evaluated, and then compared with Scan-Based Algorithm (SBA) and Completed Random Algorithm (CRA) in terms of time consumption. And the experiments indicate SBA-RA outweighs the others. In the end, future possibilities to improve SBA-RA are discussed.